(untitled) (Research, Society and Development, 2020)
Sweet potato is one of the seven major staple crops in the world. Although most cream-fleshed sweet potatoes are produced locally, orange-fleshed sweet potato (OFSP) is an excellent source of beta-carotene and can be promoted to alleviate vitamin A deficiency. The aim of this study was to evaluate the retention of total carotenoids (TC) and all-trans-beta-carotene (ATBC) after processing and storage of cookies with different proportions of OFSP and margarine. Cookies formulated with 18 to 22.23 g/100 g of OFSP and 28.57 to 34.6 g/100 g of margarine were analyzed by spectrophotometry and high-performance liquid chromatography. The formulation containing the highest content of OFSP (22.23 g/100 g) and 32.84 g/100 g of margarine showed greater retention of TC and ATBC after processing. Among the other samples with the same proportion of OFSP, the one containing the highest margarine concentration (34.6 g/100 g) has shown a greater capacity to maintain TC and ATBC during storage (up to 56 days), demonstrating lipids important role in the preservation of these components.